Mukhtalif al-Ḥadīts dan Cara Penyelesaiannya Perspektif Ibn Qutaybah - Masykur Hakim (ILMU USHULUDDIN, 2015)
This article is explanation on Ibn Qutayba in giving a solution for the problem when the content of Ḥadīths (Sunna) is contradictory to or conflicted with the Qur’ān, reason, logic or to the principles of natural sciences. The experts of Ḥadīth mentioned them as the contradictive Ḥadīths. In this respect, Ibn Qutayba observed that the contradictive Ḥadīth can be given a solution in many sides. If the contradiction happened thence one needs an interpretation until the understanding of the Ḥadīth remains suitable to the purpose of al-Qur’ān. In his masterpiece work Ta’wīl Mukhtalif al-Ḥadīth, he has noted many examples of the contradictive Ḥadīth and gave the ways to solve them in order the Ḥadīth easily to comprehend by the umma. He offered various approaches to the contradictive Ḥadīth, some of them are rational and logical, but some of them are irrational and difficult to understand by today modern society.